Mapping the research landscape of game-centred approaches in physical education: a bibliometric analysis - Maulidin; Syah, Herman (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Game-Centred Approaches (GCAs) have gained prominence in Physical Education (PE) for their potential to enhance student engagement, motivation, and learning outcomes. However, their implementation still faces pedagogical and institutional challenges. Despite growing interest, a comprehensive understanding of research trends and knowledge structures in this area remains limited. This study addresses that gap. Research Objectives: This study aims to analyse the related literature implementation of GCAs in PE teaching, identify past and current research trends and attempt to predict possible future research trends. Methods: A bibliometric approach was employed using data sourced from the Scopus database. VOSviewer software was utilized to visualize co-authorship, keyword co-occurrence, and thematic clusters, allowing identification of influential authors, institutions, and evolving research topics. Findings/Results: The analysis revealed increasing scholarly attention toward GCAs as tools for developing students’ holistic learning—cognitive, social, and motor domains. Key themes included improving motor skills, decision-making, and tactical understanding through games. Recent trends also emphasize the importance of teacher training and professional development as critical to the effective integration of GCAs in PE. Conclusion: GCAs contribute significantly to the enhancement of student learning in PE. However, successful implementation depends on teacher readiness and ongoing pedagogical innovation. This study offers strategic insights for educators, curriculum designers, and researchers seeking to expand the application and impact of GCAs in physical education.